2015
DOI: 10.1016/j.cell.2015.07.056
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Demethylating Agents Target Colorectal Cancer Cells by Inducing Viral Mimicry by Endogenous Transcripts

Abstract: Summary DNA demethylating agents have shown clinical anti-tumor efficacy via an unknown mechanism of action. Using a combination of experimental and bioinformatics analysis in colorectal cancer cells, we demonstrate that low-dose 5-AZA-CdR targets colorectal cancer initiating cells (CICs) by inducing viral mimicry. This is associated with induction of dsRNAs derived at least in part from endogenous retroviral elements, activation of the MDA5/MAVS RNA recognition pathway and downstream activation of IRF7. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

91
1,315
12
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,219 publications
(1,423 citation statements)
references
References 38 publications
91
1,315
12
5
Order By: Relevance
“…These elevated dsRNA species were mostly found in introns, corroborating known transcriptome‐wide HNRNPC binding regions (Konig et al , 2010; Zarnack et al , 2013). This differs from previous observation of elevated dsRNA derived from normally hypermethylated endogenous retroviruses (ERVs) that are activated by anti‐tumor inhibitors to trigger the IFN response as a therapeutic approach (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Heterogeneous nuclear ribonucleoprotein C is well known for its function in regulating RNA splicing by binding with introns, especially the introns containing Alu (Konig et al , 2010; Zarnack et al , 2013).…”
Section: Introductioncontrasting
confidence: 80%
See 3 more Smart Citations
“…These elevated dsRNA species were mostly found in introns, corroborating known transcriptome‐wide HNRNPC binding regions (Konig et al , 2010; Zarnack et al , 2013). This differs from previous observation of elevated dsRNA derived from normally hypermethylated endogenous retroviruses (ERVs) that are activated by anti‐tumor inhibitors to trigger the IFN response as a therapeutic approach (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Heterogeneous nuclear ribonucleoprotein C is well known for its function in regulating RNA splicing by binding with introns, especially the introns containing Alu (Konig et al , 2010; Zarnack et al , 2013).…”
Section: Introductioncontrasting
confidence: 80%
“…However, in our work done in different types of breast cancer cells, expression profiles of the down‐stream genes indicated that NOTCH3 signaling was not amplified when interferon signaling was activated. On the other hand, several other studies have reported that up‐regulated dsRNA from endogenous retrovirus (ERV) in tumor cells, triggered by DNA methyltransferase inhibitors or CDK4/6 inhibitors, induced IFN responses and thus inhibited tumor development (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017). Our proposed model is similar to these studies, even though the dsRNA species in our study were originated from a different resource than ERV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This "DNA methylation paradox", recapitulates epigenomic states in normal germ cells, and provides the rationale for the development of epigenetic regimens that induce growth arrest/apoptosis via restoration of tumor suppressor gene expression (106)(107)(108), while simultaneously augmenting antitumor immunity by up-regulation of CTAs (79), induction of viral mimicry by de-repression of endogenous retroviruses (109,110), and modulation of the tumor microenvironment (111)(112)(113).…”
Section: Epigenetic Strategies For Mesothelioma Therapymentioning
confidence: 99%